Deciphering the underlying immune network of the potato defense response inhibition by Phytophthora infestans nuclear effector Pi07586 through transcriptome analysis - Xiong, Yumeng; Zhao, Di; Chen, Shengnan; Yuan, Lan; Zhang, Die; Wang, Hongyang (Frontiers in Plant Science, 2023)
Phytophthora infestans, a highly destructive plant oomycete pathogen, is responsible for causing late blight in potatoes worldwide. To successfully infect host cells and evade immunity, P. infestans secretes various effectors into host cells and exclusively targets the host nucleus. However, the precise mechanisms by which these effectors manipulate host gene expression and reprogram defenses remain poorly understood. In this study, we focused on a nuclear-targeted effector, Pi07586, which has been implicated in immune suppression. Pi07586 showed significant up-regulation during the early stages of infection and was nuclear-localized. Overexpression of Pi07586 resulted in increased leaf colonization by P. infestans. RNA-seq analysis revealed that Pi07586 effectively suppressed the expression of PR-1C-like and photosynthetic antenna protein genes. Furthermore, our analysis indicated that Pi07586 overexpression led to a substantial decrease in abscisic acid (ABA), jasmonic acid (JA), and jasmonoyl-isoleucine (JA-Ile) levels, while not affecting salicylic acid (SA) and indole-3-acetic acid (IAA) production. These findings shed new light on the modulation of plant immunity by Pi07586 and enhance our understanding of the intricate relationship between P. infestans and host plants.